A Survey on Multi-path Routing Protocols in Wireless Multimedia Sensor Networks - Enyan Sun; Chuanyun Wang; Feng Tian (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Single-path routing protocols cannot satisfy the need of Wireless multimedia Sensor networks, and Multi-path routing protocols have many advantages in wireless multimedia sensor networks. Recent years, some researchers have proposed many multi-path routing protocols. The paper introduces and outlines the different multi-path routing protocols in WMSNs and classifies them according to their characteristics. The future direction is pointed.